Вміст ферменту каталази в ґрунті на території АЗС м. Рівного - Стернік, Віта; Марциновський, Віталій; Мельник, Віра; Sternik, Vita; Martsinovsky, Vitalii; Melnik, Vira (Східноєвропейський Національний університет імені Лесі Українки, 2015)
У статті досліджено ступінь збагачення ґрунту ферментом каталази в районі розміщення автозаправних станцій в м. Рівному. Відповідно до шкали оцінки ступеня збагачення ґрунту ферментами встановлено, що більшість ґрунтів на території АЗС міста охарактеризовані середнім та низьким ступенем збагаченості ґрунту ферментом каталази.The studying of the activity of soil enzymes acquires practical importance and serves as an indicator of biochemical processes in edaphotope was studied, additional diagnostic indicator of soil fertility. In the research it was of soil enrichment near the gas station in Rivne by the enzyme catalase. It was established that in the sample layers the activity in different soil layers is different. It was recorded that in some samples from the upper horizon (0–20 cm) of soil biological activity in more than three times lower than in horizon layers (21–40 cm) in some samples of the soil (21 to 40 cm) it was fixed low rate of the enzyme catalase, indicating significant contamination of the soil. According to the scale of assessment of enzymes soil enrichment, it were obtained the following results: the majority of the analyzed soils in the territory of the gas station in Rivne is characterized by medium and low degree of enzyme enrichment catalase.
The Content of the Enzyme Catalase in the Soil on the Territory of the Gas Station Rivne.
Keywords: збагачення ґрунту ферментом каталази; забруднення; АЗС; оцінка.; enrichment of soil enzyme catalase; pollution; gas stations; evaluation